Factors affecting rice domestic production output in Preah Vihear province, Cambodia: A study using OLS regression model - Darith, Siek; Eav, Lim Kim; Ngath, Sophorn; Sourphimean, Siek; Sourchhordaphear, Siek (International Journal of Sustainable Agricultural Research, 2024)
This study explores the attitudes of domestic farmers toward rice production practices and identifies factors affecting rice yields in Preah Vihear Province. Cambodia’s economy is heavily reliant on rice cultivation. Rice is a staple food and a major export, significantly contributing to the nation’s food security. However, rice production in the entire country faces challenges such as limited irrigation, small farm sizes, and geographical constraints. Preah Vihear province, a remote, mountainous area in northern Cambodia bordering Thailand and Laos, is a key rice-producing region characterized by hilly terrain and small-scale farming. Known for its stunning natural beauty and the famous Preah Vihear Temple, a UNESCO World Heritage site, the province offers unique opportunities for farmers to increase their income and gain access to international markets through distinctive and renowned rice seeds. To better understand factors affecting rice domestic production in Preah Vihear, a primary statistical ordinary least squares (OLS) model will be applied to analyze rice output and related variables. The findings of this study are instrumental in developing targeted strategies that aim to enhance rice yields and improve the livelihoods of rural farmers. By identifying key controllable factors, farmers can make informed decisions to increase their profits, ensure sustainable rice production, and contribute to the overall economic growth of farming communities.